Insights into the different effects of food on intestinal secretion using magnetic resonance imaging - Wilkinson-Smith, Victoria C.; Major, Giles; Ashleigh, Lucy; Murray, Kathryn; Hoad, Caroline L.; Marciani, Luca; Gowland, Penny A.; Spiller, Robin C. (Wiley, 2018)
Background